2016
DOI: 10.1155/2016/3560812
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Chinese Herbal Medicine Induced Liver Injury

Abstract: Background. In recent years, with the popularity of CHM, its hepatotoxicity has also been increasingly noticed. However, there are still veils on causative herbs and clinical characteristics. Aim. To systematically review data on CHM induced liver injury with particular focus on causative herbs and clinical characteristics. Methods. Using terms related to CHM and liver injury, PubMed and three Chinese electronic databases were searched, which was limited to the past 5 years. Publications meeting our eligibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 38 publications
4
26
0
6
Order By: Relevance
“…Herbal medicines are often considered safe because of their natural content, whereas remedies such as guggul herbal medicine, svarnabhasma, race maniknya, ginger (zingeber officinale), gingko biloba (gingko), ginseng, St. Johns wort, godanti, echinacea purpurea, lavanabhaskar, parad preparations, Timothy grass and andrographis paniculata, among others, can cause hypersensitive reactions. 18,23,24 Studies have shown that such reactions to harmful herbal medicine often occur between the ages of 18 and 44 years. In this particular case, the patient was 43 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal medicines are often considered safe because of their natural content, whereas remedies such as guggul herbal medicine, svarnabhasma, race maniknya, ginger (zingeber officinale), gingko biloba (gingko), ginseng, St. Johns wort, godanti, echinacea purpurea, lavanabhaskar, parad preparations, Timothy grass and andrographis paniculata, among others, can cause hypersensitive reactions. 18,23,24 Studies have shown that such reactions to harmful herbal medicine often occur between the ages of 18 and 44 years. In this particular case, the patient was 43 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Um verlässliche Schlussfolgerungen aus diesen Berichten ableiten zu können, ist eine detaillierte Dokumentation essentiell [1]. Die Qualität von Fallberichten lässt jedoch oft zu wünschen übrig [1][2][3][4] An eine Beurteilung pflanzlicher Produkte sind dabei besondere Anforderungen zu stellen, die überwiegend nicht erfüllt werden. Häufig ist das verdächtigte Produkt unzureichend charakterisiert [1], [3], d.h. es fehlten die genaue(n) botanische(n) Bezeichnung(en), der Pflanzenteil, der Hersteller, die Authentifizierung der Droge(n) oder der Ausschluss von Kontaminationen und Verfälschungen.…”
Section: Besonderheiten Der Kausalitätsermittlung Bei Pflanzlichen Prunclassified
“…Die Qualität von Fallberichten lässt jedoch oft zu wünschen übrig [1][2][3][4] An eine Beurteilung pflanzlicher Produkte sind dabei besondere Anforderungen zu stellen, die überwiegend nicht erfüllt werden. Häufig ist das verdächtigte Produkt unzureichend charakterisiert [1], [3], d.h. es fehlten die genaue(n) botanische(n) Bezeichnung(en), der Pflanzenteil, der Hersteller, die Authentifizierung der Droge(n) oder der Ausschluss von Kontaminationen und Verfälschungen. Will man nicht nur den Zusammenhang zwischen einem Produkt als solchem und der Arzneimittelreaktion nachweisen, sondern sich auch auf bestimmte in dem Produkt enthaltene pflanzliche Bestandteile beziehen, dann ist die exakte Kenntnis der Zusammensetzung einschließlich Bestätigung der enthaltenen Arzneidroge(n) und möglicherweise nicht deklarierter Inhaltsstoffe erforderlich.…”
Section: Besonderheiten Der Kausalitätsermittlung Bei Pflanzlichen Prunclassified
See 1 more Smart Citation
“…lobata was full of secondary metabolites such as isoflavonoids (Rong et al 1998;Joung et al 2003), flavones (Kinjo et al 1988), triterpenoids (Arao et al 1995(Arao et al , 1997, and dibenzyl butyrolactones (Hirakura et al 1997). It had the efficacy of cytoprotective activity (Heo et al 2019), hepatoprotective effect (Abascal and Yarnell 2007;Zhang et al 2016;Sun et al 2018), antineoplastic activity (Zhang et al 2019), antimicrobial activity (Joung et al 2003), anti-tobacco mosaic virus activity (Cui et al 2018), relieving muscles analgesia, reducing fever and antidiarrheal (Li 2015), treating diabetes and cardiovascular diseases (Wong et al 2011;Liu et al 2019), and so on. The isoflavonoids are also common constituents in human diets (Joung et al 2003).…”
mentioning
confidence: 99%